Potential utilization of oil shale as a stabilizing material for compressed Earth block - Al-Fhaid, Hamza; Edris, Walid Fouad; Al-Tamimi, Mahmoud (Frontiers in Built Environment, 2023)
This research aims to produce a compressed Earth block (CEB) product locally from soil collected from North Jordan. The CEB mixture was further stabilized using oil shale (OS) and ordinary Portland cement (OPC). The CEB specimens were thoroughly characterized by studying their mechanical properties (compressive and flexural strength) and durability characteristics (erosion, absorption, and shrinkage tests). Eight mixtures were carried out for the CEB, one of which was the control mix. The other mixtures were carried out by replacing soil with OS, cement, and sand in different proportions. The results showed that higher compressive strength and flexural strength for CEB were obtained in the mixtures that contained 10% of OS and 10% of cement, resulting in an average compressive strength of 10.6 MPa and flexural strength of 0.25 MPa. The absorption increased when the OS increased in the soil. The consequent erosion test was related to the absorption test, where the higher the absorption, the more negative the results of the erosion test. Moreover, oil shale improved the shrinkage properties of the CEB, as the higher the proportion of oil shale in the CEB, the lower the shrinkage. Finally, using oil shale as a stabilizing agent in soil had a clear role in improving the mechanical properties, hiding the shrinkage cracks, and reducing the volume shrinkage value of the CEB.